Ti-ZEL in Action: A Mix-Method Study Redefining English-Speaking Abilities for Academic Staff - Rahmiani, Nur; Mawaddah, Syarifah; Nadiah, Faqihatun; Nordin, Zaimuariffudin Shukri (Eralingua: Jurnal Pendidikan Bahasa Asing dan Sastra, 2025)
Abstract. This study highlights the effectiveness of the Time Zone in English Language (Ti-ZEL) program in improving speaking abilities among academic staff at one of the public universities in Pontianak, Indonesia. This was a mixed-method study that included some participants with provoked tests and treatments. Other forms of observation and interviews were conducted to evaluate the overall obstacles and success factors of the Ti-ZEL program. The program significantly improved speaking abilities with measurable progress (p < 0.001). The findings underscore the importance of providing opportunities and supportive environments for English practice within habituation programs. Success factors included respondents' basic English skills, an engaging and practical approach, and consistent commitment. Challenges included technical and non-technical barriers, limited proficiency, internal factors (job exhaustion, mental strain), and external distractions (workload, other activities). This cultivated approach greatly governs the level of skill improvement in speaking English. This strongly concludes the necessity of enhancing the English language skill among the academic staff of the university using the Ti-ZEL habituation model. Implementing this approach to the academic staff was new and at first unfamiliar but it proved to be successful.Keywords: Ti-ZEL, English habituation program, speaking abilities, academic staff